Pengaruh Beberapa Indeks Saham dan Indikator Ekonomi Global Terhadap Kondisi Pasar Modal Indonesia - Andiyasa, I Gusti Agus; Purbawangsa, Ida Bagus Anom; Rahyuda, Henny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
Indonesian capital market is highly developed capital markets in recent years. With the growing world of investment and finance , the events that occurred in other countries, be it stock index or economic indicator will have an impact to the Indonesian state. This study aimed to determine the effect of several stock indices and global economic indicators to the condition of the Indonesian Capital Market. Global stock indices used in this study is the Dow Jones index, Nikkei 225 index, Shanghai Composite Index ( SSE ), UK : FT100 index. Global economic indicators used include oil prices, gold prices, and exchange rate USD/IDR. This study used multiple linear regression analysis. The results of this study indicate that the Dow Jones index, Shanghai index, and UK : FT100 index positive effect on JCI, while the Nikkei 225 index variable, world oil prices, gold prices, and the exchange rate USD/IDR negatively affect the JCI movement. Future studies may add to the index of other countries and other economic indicators. Keywords: Global stock indices, global economic indicator, JCI